Meta Analysis: The Effect of Project-based Learning on Studentsâ€™ Learning Outcomes in Chemistry Learning - Desyafrianti, Vanny; Aini, Faizah Qurrata (Hydrogen: Jurnal Kependidikan Kimia, 2024)
One of instructional model which can be implemented in Merdeka Curriculum is Project-based Learning (PjBL). In this model, students design a project based on their contextual understanding, thus having an impact on learning outcomes especially in knowledges aspect. Using meta-analysis with PRISMA method, researchers have traced various research articles and proceedings from 2020 to 2024 by using Publish or Perish with the keywords â€œproject-based learningâ€, â€œlearning outcomesâ€, â€œchemistryâ€, â€œpjblâ€, â€œhasil belajarâ€, â€œkimiaâ€. There are 200 articles found, after going through several stages there are seven articles that are the subject of this research. By calculating the effect size value of each study, the average effect size result was 1.1825 which was included in the high category. For summary that, the Project-based Learning model has an affect on student learning outcomes in chemistry learning, especially on the topics of acids and bases, colloids, chemical equilibrium, chemical bonds, solutions and thermochemistry.